Disaggregating Fatal and Non-Fatal Shootings in Boston, 2015-2023 - Piquero, Alex R.; Wheeler, Andrew (International Journal of Police Science, 2024)
Community gun violence is a serious public safety issue. Unfortunately, limitations surrounding data on shootings have made it difficult for members of the public and the research community to understand the nature and trends associated with gun violence and have also hampered policy officials' attempts to reduce the incidence of shootings. This paper makes use of shooting data from the Boston Police Department that contains the location of the shooting as well as whether the shooting was fatal or non-fatal. Results show that two police districts, Roxbury and Mattapan, account for over half of the shootings and that the risk of being fatally shot in these two districts for a black male is almost double that in other districts. Findings have implications for police allocations as well as policy interventions.